2013
DOI: 10.1055/s-0033-1361090
|View full text |Cite
|
Sign up to set email alerts
|

A Liquid Chromatography Tandem Mass Spectrometry Based Regulatory Compliant Method for the Determination of Tenofovir in Human Serum

Abstract: A simple, rapid, and specific assay based on solid phase extraction and liquid chromatography-electrospray ionization tandem mass spectrometry (LC-ESI MS-MS) for the quantitative analysis of Tenofovir in human serum using Tenofovir D6 as internal standard (IS) have been developed. The precursor to product ion transitions of m/z 288.2/176.2 and m/z 293.9/182.3 used to measure the analyte and internal standard (Tenofovir and Tenofovir D6). The method was validated over a concentration range of 5.06-603.72 ng mL(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Our study is simple to be used in routine laboratories and its analysis time is short [8]. Our study is suitable for green chemistry compared to the studies in the literature [15,30,32].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our study is simple to be used in routine laboratories and its analysis time is short [8]. Our study is suitable for green chemistry compared to the studies in the literature [15,30,32].…”
Section: Discussionmentioning
confidence: 91%
“…In the literature, tenofovir has been determined as the only active ingredient and in combination with other active ingredients. These methods include HPLC [3][4][5][6][7][8], HPLC-MS [9], HPLC-MS/MS [10,11], LC-MS [12][13][14], LC-MS/MS [15][16][17][18], UPLC [19][20][21][22][23][24][25], UPLC-MS and UPLC-MS/MS [22][23][24][25], TLC [26], HPTLC [27][28][29], and spectrophotometric [7,[30][31][32][33][34] methods. This paper describes new, simple, sensitive, and rapid spectrofluorimetric method for the determination of tenofovir in pharmaceutical dosage form.…”
Section: Introductionmentioning
confidence: 99%
“…Literature survey revealed that few chromatographic methods for SOLS [6][7][8][9][10][11][12][13][14][15][16][17], FLXHC [18][19][20][21] and TOLT [22][23][24][25][26][27][28][29], spectrophotometric methods for SOLS [30,31], FLXHC [32,33] and TOLT [34][35][36], potentiometric method Equivalent weights of 10 mg of SOLS, 20 mg of FLXHC and 20 mg of TOLT were transferred into three 100 mL clean dry volumetric flasks containing 70 mL of mobile phase and the mixture was sonicated to dissolve the powder. The volume was made up to the mark with the same solvent.…”
Section: Preparation Of Pharmaceutical Dosage Forms Solutionsmentioning
confidence: 99%
“…Tenofovir and emtricitabine inhibit Human Immuno-deficiency Virus (HIV) reverse transcriptase and lower the amount of HIV in the body. They are administered together as part of highly active antiretroviral therapy (HAART) [5,6]. A bioanalytical method is needed to determine drug concentrations in biological fluids like plasma for purposes of therapeutic drug monitoring and pharmacokinetic studies.…”
Section: Introductionmentioning
confidence: 99%